2018
DOI: 10.1093/ofid/ofy210.2110
|View full text |Cite
|
Sign up to set email alerts
|

2457. Multivariate Analyses of Socio-Economic Inequities in Parental Awareness and Utilization of Meningococcal Serogroup B Vaccines

Abstract: BackgroundIn 2015, the US Advisory Committee on Immunization Practices (ACIP) made a Category B recommendation for serogroup B meningococcal (MenB) vaccines for adolescents 16–18 years. In 2016, MenB caused ~60% of invasive meningococcal disease among US individuals 16–23 years old; however, utilization of MenB vaccines was much lower than other vaccines with Category A recommendations. Therefore, we examined factors associated with awareness and utilization of MenB vaccines.MethodsAn online quantitative surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For MenB vaccination, a survey of 619 US parents of 16–19-year-olds reported an HCP recommendation as the most influential factor in predicting MenB vaccination status [ 28 ]. Parents who received a recommendation from a provider were 4.8 times more likely to vaccinate their child and 5.7 times more likely to have an adolescent already vaccinated versus parents who did not receive a recommendation [ 30 ]. Finally, a survey of 445 parents of children attending high school in Minnesota reported that a top reason their child had not received a MenACWY or MenB vaccine was because their HCP did not recommend the vaccine (33.9% and 32.7%, respectively) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For MenB vaccination, a survey of 619 US parents of 16–19-year-olds reported an HCP recommendation as the most influential factor in predicting MenB vaccination status [ 28 ]. Parents who received a recommendation from a provider were 4.8 times more likely to vaccinate their child and 5.7 times more likely to have an adolescent already vaccinated versus parents who did not receive a recommendation [ 30 ]. Finally, a survey of 445 parents of children attending high school in Minnesota reported that a top reason their child had not received a MenACWY or MenB vaccine was because their HCP did not recommend the vaccine (33.9% and 32.7%, respectively) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional recent US studies have reported this same association along the continuum of MenB vaccine awareness, intent to vaccinate, and receipt. A nationally representative survey of 619 parents of 16-19-year-olds demonstrated that awareness of MenB vaccines and interest in potentially vaccinating was significantly higher among those aware of MenACWY vaccines [17]. A regional cross-sectional survey of 445 parents of adolescents found that an equivalent percentage of parents were willing to vaccinate their teens with MenACWY and MenB vaccines (58.6% and 55.1%, respectively) and were seeking advice from their provider (79.6% and 81.1%) [18].…”
Section: Discussionmentioning
confidence: 99%